2018
DOI: 10.1111/sltb.12537
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Relationships Buffer Suicidality in National Guard Service Members: A Longitudinal Study

Abstract: Objective Members of the U.S. military are at a high suicide risk. While studies have examined predictors of suicide in the U.S. military, more studies are needed which examine protective factors for suicide. Informed by the interpersonal theory of suicide, this study examined the strength of the intimate relationship and its role as a buffer of suicidality in National Guard service members. Method A total of 712 National Guard residing in a Midwestern state, who had all recently returned home from a deploymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
1
11
2
Order By: Relevance
“…Our findings contradicted the findings from Blow et al (2018), who observed that higher PTSD and depression severity, coupled with lower intimate relationship satisfaction, increased risk for suicide. It is possible that the association of relationship satisfaction with suicidal ideation differs by gender.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings contradicted the findings from Blow et al (2018), who observed that higher PTSD and depression severity, coupled with lower intimate relationship satisfaction, increased risk for suicide. It is possible that the association of relationship satisfaction with suicidal ideation differs by gender.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings revealed that lower intimate relationship satisfaction was associated with the presence of suicidal ideation above and beyond the effects of PTSD, depression, and covariates. These findings are consistent with leading theories that highlight the contribution of interpersonal distress on suicide risk (e.g., Joiner, 2005), and previous findings showing that interpersonal distress can elevate suicide risk (Blais et al, 2018; Blow et al, 2018; Bush et al, 2013; Griffith, 2012). Higher depression and PTSD severity were also associated with the presence of suicidal ideation, which is consistent with previous research in military samples (Elbogen et al, 2018; Langhinrichsen‐Rohling et al, 2011; U.S. Department of Veterans Affairs, 2019b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, civilian research shows that the prevalence rate for PTSD among females is higher than the prevalence rate observed in males (see reviews, Brewin, Andrews, & Valentine, 2000; Ditlevsen & Elklit, 2012; Greene, Neria, & Gross, 2016; McLean & Anderson, 2009; Tolin & Foa, 2006), which may be due, in part, to having a higher likelihood of exposure to sexual violence (Frans, Rimmö, Åberg, & Fredrikson, 2005; Perrin et al, 2014). Finally, satisfying romantic relationships can buffer against suicidal ideation (e.g., Blow, Ganoczy, Walters, & Valenstein, 2018) and psychological distress (e.g., Taft et al, 2011), and emerging data reveals that among female SM/Vs, poorer relationship satisfaction is associated with increased suicide risk above and beyond the effects of PTSD and depression (Blais, 2019a). These studies highlight the critical need to further understand the association of PTSD symptom clusters and relationship satisfaction in females.…”
Section: Introductionmentioning
confidence: 99%
“…Post-deployment studies of U.S. National Guard personnel have found that good intimate relationships are associated with all mental health indicators -PTSD, depression, and anxiety (Blow et al, 2019). Therefore, interventions that promote the strengthening of intimate interpersonal relationships have the potential to reduce military suicide rates.…”
mentioning
confidence: 99%